Transformation of Fiqh Learning in the Digital Era: Integration of Religious Moderation and Islamic Legal Literacy in Islamic Religious Education - Abdul Rahman; Angga Aldilla Gussman; Siti Marisa; Aat Ruchiat Nugraha (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
The digital era has brought fundamental changes to educational practices, including the teaching of fiqh as a core component of Islamic Religious Education (PAI). This article presents a systematic literature review on the transformation of fiqh learning in the digital age, with a particular focus on the integration of religious moderation values and the strengthening of Islamic legal literacy. The study employs the Systematic Literature Review (SLR) method using the PRISMA protocol, identifying 28,794 articles from various academic databases. Following a multi-stage screening process conducted independently by two reviewers, with inter-rater agreement measured by Cohen’s Kappa (κ = 0.82), a total of 50 articles met the inclusion criteria for in-depth analysis. Methodological quality assessment was performed using the CASP checklist adapted for review studies. The findings indicate that digital platforms significantly enhance student engagement, critical thinking, and religious literacy. The integration of religious moderation values into the PAI curriculum has proven effective in fostering inclusive attitudes and countering radicalism. This article recommends a holistic approach that combines curriculum reform, continuous professional development for teachers, and contextual technological innovations grounded in Sharia-based values.